Endophytic fungi from medicinal plant Bauhinia forficata : Diversity and biotechnological potential - Bezerra, Jadson D.P. (Sociedade Brasileira de Microbiologia, 2015)

(untitled) (Braz J Microbiol)
Bauhinia forficata is native to South America and used with relative success in the folk medicine in Brazil. The diversity, antibacterial activity, and extracellular hydrolytic enzymes of endophytic fungi associated with this plant were studied. Plant samples, which included leaves, sepals, stems, and seeds, were used. Ninety-five endophytic fungal were isolated (18 from leaves, 22 from sepals, 46 from stems, and nine from seeds), comprising 28 species. The most frequently isolated species were Acremonium curvulum (9.5%), Aspergillus ochraceus (7.37%), Gibberella fujikuroi (10.53%), Myrothecium verrucaria (10.53%) and Trichoderma piluliferum (7.37%). Diversity and species richness were higher in stem tissues, and Sorensen’s index of similarity between the tissues was low. Eleven fungi showed antibacterial activity. Aspergillus ochraceus , Gibberella baccata , Penicillium commune , and P. glabrum were those with the greatest antibacterial activity against Staphylococcus aureus and/or Streptococcus pyogenes . Thirteen species showed proteolytic activity, particularly Phoma putaminum . Fourteen species were cellulase positive, particularly the Penicillium species and Myrmecridium schulzeri . All isolates tested were xylanase positive and 10 showed lipolytic activity, especially Penicillium glabrum . It is clear that the endophytic fungi from B. forficata have potential for the production of bioactive compounds and may be a source of new therapeutic agents for the effective treatment of diseases in humans, other animals, and plants. To our knowledge, this is the first study of endophytic fungi from different tissues of B. forficata and their biotechnological potential.